Gadih Batanduak - Yuliana Nasution (Saraswati)
“Gadih  Batanduak” derived  from Minangkabau  language  which means the horned girl. A dance work which grew out of the ideational stimulation on empirical experience of the choreographer as a Minang girl who lives in a country town. In Minangkabau  view, woman  is the cornerstone  of the existence  of the mores that embrace the matrilineal system. Minangkabau  women have the right of marriage, tribal, or inheritance. Regulations and limitations as applied by the Minang woman prepares the heir of the family to be proud of Alam Minangkabau. Choreographer,  as  Minangkabau  descent  girl  inherits  the  limitations  of the situation  with  all  the  regulations  that  have  been  invested  by  the  family  since childhood. This regulation is considered archaic and unreasonable to city life, and lead to the inconvenience. The prejudice was finally changed when the choreographer returned to her hometown in Lintau, Tanah Datar, West Sumatra. The limitation is even more evident when the process of adaptation to neighborhood and surrounding communities. However, the inconveniences gradually turned into an impressive admiration and homesick after returned to the city.